PENGEMBANGAN MEDIA AJAR MATEMATIKA DENGAN MENGGUNAKAN MEDIA MICROSOFT VISUAL BASIC UNTUK MENINGKATKAN KEMAMPUAN MATEMATIS MAHASISWA (Adopsi Langkah Teori Pengembangan Borg & Gall) - Rinaldi, Achi (JURNAL e-DuMath, 2018)
AbstractThe purpose of this study is to determine the development of mathematics teaching materials on matrix materials using Microsoft Visual Basic media that is easy to understand learners and quality according to expert materials and programming experts. Based on the assessment of material experts, these teaching materials are included in the criteria very well, with a feasibility level of 87%. Based on the assessment of media experts, this resource is included in very good criteria, with a degree of eligibility of 88%. Based on the results of the test on the learners, this instructional material is included in the criteria very well, with a feasibility level of 86%. Based on the assessment of educational practitioners, these teaching materials are included in very good criteria, with a feasibility level of 86%. So it can be concluded that the end result of the development of this resource is suitable to be used as teaching material of Algebra Liner on matrix material. The final product of this resource is a product that has passed the first and second revision stage. This resource is software that runs on Windows XP, Seven, 77 and Windows 8 and the name "SolusiMatrix".Keywords: Matrix, programming, Microsoft Visual Basic..Â